Therapeutic drug monitoring and neutralizing anti-drug antibody detection to optimize TNF-alpha inhibitor treatment for uveitis - Chen, Howard C.; Shunyakova, Jenny; Reddy, Amit K.; Pandiri, Srujay; Hassman, Lynn (Frontiers in Ophthalmology, 2025)
BackgroundAdalimumab taken every other week is an effective treatment in patients with chronic refractory uveitis. Patients who have a suboptimal response to this treatment may suffer from recurrent inflammation and vision loss. Here, we investigated the use of therapeutic drug monitoring and neutralizing anti-drug antibody detection as a strategy to optimize tumor necrosis factor (TNF)-alpha inhibitor treatment in patients who have a suboptimal response to the initial dosing of adalimumab.MethodRetrospective cohort study performed in two tertiary referral uveitis services in the United States between 2015 to 2023. Patients with non-infectious uveitis who had a suboptimal response to every two-week dosing of adalimumab and underwent serum adalimumab level with reflex to anti-drug antibody testing were followed. Patients were considered to have neutralizing drug antibodies when serum drug levels were low (less than or equal to 6 mcg/mL) and anti-adalimumab antibodies were present on reflex testing. Treatment adjustment was made by clinicians with the knowledge of serum adalimumab level and the presence or absence of neutralizing drug antibodies. Every two-week dosing of adalimumab was either escalated to weekly dosing or switched to infliximab, an alternate TNF-alpha inhibitor, based on these findings. The primary outcome was success or failure at 12 months, as determined by disease inactivity on steroid-sparing therapy.Results32 patients with suboptimal response to the initial dosing of adalimumab were included. 31.2% (n=10) of patients were found to have neutralizing drug antibodies. All patients with neutralizing drug antibodies underwent a medication switch to infliximab with a remission rate of 40% at 12 months. Patients without neutralizing drug antibodies (n=22) underwent dose escalation (77.3%; n=17) or medication switch (22.7%; n=5) and achieved a remission rate of 68.2% at 12 months. Altogether, treatment adjustment based on therapeutic drug monitoring and neutralizing drug antibody detection, in our cohort, resulted in a remission rate of 62.5%.ConclusionsFor patients with uveitis experiencing suboptimal therapeutic response to adalimumab dosed every two weeks, therapeutic drug monitoring and neutralizing drug antibody detection may help clinicians optimize TNF-alpha inhibitor treatment.